Kinetic Study of Zirconia-Alumina-Supported Ni-Fe Catalyst for Dry Reforming of Methane: Impact of Partial Pressure and Reaction Temperature - Ahmed Al-Fatesh; Kenit Acharya; Ahmed I. Osman; Ghzzai Almutairi; Anis Hamza Fakeeha; Ahmed Elhag Abasaeed; Yousef A. Al-Baqmaa; Rawesh Kumar (International Journal of Chemical Engineering)
A better understanding of the reaction mechanism and kinetics of dry reforming of methane (DRM) remains challenging, necessitating additional research to develop robust catalytic systems with high catalytic performance, low cost, and high stability. Herein, we prepared a zirconia-alumina-supported Ni-Fe catalyst and used it for DRM. Different partial pressures and temperatures are used to test the dry reforming of methane reaction as a detailed kinetic study. The optimal reaction conditions for DRM catalysis are 800°C reaction temperature, 43.42 kPa CO2 partial pressure, and 57.9 kPa CH4 partial pressure. At these optimal reaction conditions, the catalyst shows a 0.436 kPa2 equilibrium constant, a 0.7725 molCH4/gCat/h rate of CH4 consumption, a 0.00651 molCH4/m2/h arial rate of CH4 consumption, a 1.6515 molH2/gCat/h rate of H2 formation, a 1.4386 molCO/gCat/h rate of CO formation. This study’s findings will inspire the cost-effective production of robust catalytic systems and a better understanding of the DRM reaction’s kinetics.